Long way down - Reynolds, Jason (2017)
As Will, fifteen, sets out to avenge his brother Shawn's fatal shooting, seven ghosts who knew Shawn board the elevator and reveal truths Will needs to know.
"A Caitlyn Dlouhy Book."
Ages 12 up.
Keywords: Novels in verse; Murder -- Fiction; Revenge -- Fiction; Ghosts -- Fiction; Brothers -- Fiction; Conduct of life -- Fiction